The Problematic Nature of Polygamy and Its Implications for the Social Status of Women in Muslim Families - Wahid, Abdul (Asian Journal of Multidisciplinary Research, 2025)
Since a long times polygamy and woman social status in islamic law often become pro and contra among muslim. Especially in gender social problem. In most cases, woman become a side who sometimes disadvantages and often experience in lowering social status from injustice and psychological pressure. This research intended to study polygamy problem to woman social status from economy aspects, psycology, culture and to identify problem that experience to polygamous women in islamic family. No less important in this research is concern in second polygamous women social status often isoleted and became bad topic either in family or society. This research used qualitative approach with literature review method and the data obtained in analysis use thematic analysis technique. From research result determine that polygamy often causing women experience being humbled in muslim family, isoleted from social community and reduced access to the economy. Another problem come from jealousy between polygamous wife, psychological pressure, and disharmony in distribution time and subsistence. Because of that, polygamy has very important problems to women scocial status espacially in the context of imbalance geschlecht issue. It’s important to have regulation and more comprehensive social approach to protect women right in muslim contemporary. So, how polygamy practice can be influence to women social status in muslim family and what problems are appear from polycamy pratice to women?